2004
DOI: 10.7164/antibiotics.57.400
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Antimalarial Activities of a Carbohydrate Antibiotic, Prumycin, against Drug-resistant Strains of Plasmodia

Abstract: K. RATA, JPMW Coordination Center, for valuable discussion. We also thank Mr. Y. KATO and Ms. M. SUZUKI, the Kitasato Institute, for the antimalarial assay, Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…[3][4][5][6][7][8] Recently, we have isolated some tropolone compounds from a culture broth of Penicillium sp. FKI-4410.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Recently, we have isolated some tropolone compounds from a culture broth of Penicillium sp. FKI-4410.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] In the course of our screening, we found borrelidin, produced by an actinomycete strain OM-0060, that proved to be more potent than chloroquine or artemether (using in vivo oral administration) against drug-resistant P. yoelii. 6 The reported biological activities of borrelidin are suggested to be the results of protein synthesis inhibition, caused by the effect on threonyl-tRNA synthetase.…”
mentioning
confidence: 97%
“…The antiplasmodial activity of marine sponge-associated microbial alkaloids has been reported by El Sayed et al (2002). Otoguro et al (2004) reported that, polysaccharides, polyketides, and polysaccharide derivatives (Prumycin) are having potential antiplasmodial activity. These findings could encourage the marine bacteria-derived compounds for the antiplasmodial drug development.…”
Section: Discussionmentioning
confidence: 99%